Patch testing to a textile dye mix by the International Contact Dermatitis Research Group - Isaksson, Marléne; Diepgen, Thomas L. (Dermatitis, 2015)
Disperse dyes are well-known contact sensitizers not included in the majority of commercially available baseline series. - Objective - To investigate the outcome of patch testing to a textile dye mix (TDM) consisting of 8 disperse dyes. - Methods - Two thousand four hundred ninety-three consecutive dermatitis patients in 9 dermatology clinics were patch tested with a TDM 6.6%, consisting of Disperse (D) Blue 35, D Yellow 3, D Orange 1 and 3, D Red 1 and 17, all 1.0% each, and D Blue 106 and D Blue 124, each 0.3%. 90 reacted positively to the TDM. About 92.2% of the patients allergic to the TDM were also tested with the 8 separate dyes. - Results - Contact allergy to TDM was found in 3.6% (1.3-18.2) Simultaneous reactivity to p-phenylenediamine was found in 61.1% of the TDM-positive patients. Contact allergy to TDM and not to other p-amino-substituted sensitizers was diagnosed in 1.2%. The most frequent dye allergen in the TDM-positive patients was D Orange 3. - Conclusions - Over 30% of the TDM allergic patients had been missed if only the international baseline series was tested. Contact allergy to TDM could explain or contribute to dermatitis in over 20% of the patients. Textile dye mix should be considered for inclusion into the international baseline series.
Gesehen am 23.06.2020